E-006 Multiple flow-related intracranial aneurysms in the setting of contralateral carotid occlusion: a case report and review of the literature. (22nd July 2019) - Mathkour, M; McCormack, E; Werner, C; Amenta, P
Abstract : Background: Severe stenosis or occlusion of one internal carotid artery (ICA) may result in increased demand and altered hemodynamics in the contralateral ICA, thus increasing the risk of IA (intracranial aneurysm) formation in the distribution of the non-stenotic artery. The prevalence of IA is higher in patients with ICA stenosis, likely due to alterations in intracranial hemodynamics. We present a patient with aneurysmal subarachnoid hemorrhage who was found to have multiple flow-related left-sided anterior circulation IA and a chronic right ICA occlusion. We discuss our patient, the considerations for management in this challenging clinical scenario, and review the literature as it pertains to the association of ICA stenosis and IA. Case presentation: A 50-year-old female with a chronic asymptomatic right ICA occlusion presented with diffuse subarachnoid hemorrhage. Emergent angiography revealed left-sided A1-A2 junction, paraclinoid, left middle cerebral artery (MCA) bifurcation, and left anterior temporal artery aneurysms. Brisk filling of the right anterior circulation via the anterior communicating artery (ACOM) was also identified, signifying increased demand on the left ICA circulation. Treatment/Result: Complete obliteration of the A1-A2 junction, paraclinoid, and MCA bifurcation aneurysms was achieved with coil embolization. The anterior temporal artery aneurysm was obliterated with clipping approximately 6 weeks following the hemorrhage. All coiled aneurysms remained obliterated at the time of the 6-week follow-up angiogram. The patient made a complete neurologic recovery and is living independently. Six-month follow-up MRA showed complete occlusion of all treated aneurysms. Conclusion: A review of published case reports/studies of patients with concurrent ICA stenosis and IA revealed a higher number of patients with multiple aneurysms contralateral (25%) to, rather than ipsilateral to (6%), the ICA stenosis. We present a patient with a chronic asymptomatic right ICA occlusion and aneurysmal SAH, who was found to have multiple, likely flow-related, left-sided anterior circulation aneurysms. All aneurysms were obliterated with a combination of endovascular and microsurgical techniques and the patient made a complete recovery. Disclosures: M. Mathkour: None. E. McCormack: None. C. Werner: None. P. Amenta: None.